﻿A striking color variation is detected in Ponera testacea Emery, 1895 (Hymenoptera, Formicidae) across its Western Palaearctic geographic range - Sándor Csősz; Kadri Kiran; Celal Karaman; Albena Lapeva-Gjonova (ZooKeys, 2022)
In this paper, we provide numeric morphology-based evidence that the dark-colored Ponera coarctata var. lucida Emery, 1898, formerly considered a synonym of P. coarctata (Latreille, 1802), is conspecific with the lighter-colored Ponera testacea Emery, 1895. Species hypotheses are developed via NC-PART clustering, combined with Partitioning Algorithm based on Recursive Thresholding (PART), and via PCA combined with gap statistics. We obtained our results from an extensive dataset from the 10 continuous morphometric traits measured on 165 workers belonging to 73 nest samples. Linear discriminant analysis (LDA) confirmed the grouping of hypotheses generated by exploratory analyses with 100% classification success when all ten morphometric traits were involved. The Anatolian Turkish black and the predominantly European yellow samples, did not separate based on their morphometric characteristics. These two color variations broadly overlap in their geographic range in Anatolian Turkey. The investigated type series of Ponera coarctata var. lucida Emery, 1898 (collected from Kazakhstan) fell within the P. testacea cluster instead of P. coarctata and is also classified with high certainty as P. testacea by confirmatory LDA. Therefore, we propose the synonymy of Ponera coarctata var. lucida Emery, 1898 with Ponera testacea Emery, 1895. As no other morphological differences than color patterns were detected between the “black” and “pale” P. testacea samples, we hold that these populations constitute geographically occurring color variations of the same species. Finally, our quantitative morphology-based results show that relying on color patterns is not a robust approach in identifying European Ponera samples, particularly in the east, but using multivariate analyses of morphometric traits is advised instead.